Involvement of a Plasmid in Production of Ropiness (Mucoidness) in Milk Cultures by Streptococcus cremoris MS - Vedamuthu, Ebenezer R. (1986)
Curing and genetic transfer experiments showed that lactose-fermenting ability (Lac(+)) and the ability to produce mucoidness in milk cultures (Muc(+)) in Streptococcus cremoris MS were coded on plasmids. The Lac(+) phenotype was associated with a 75.8-megadalton plasmid, pSRQ2201. The Muc(+) phenotype was associated with a 18.5-megadalton plasmid, pSRQ2202. The Lac plasmid, pSRQ2201, was first conjugatively transferred from S. cremoris MS to Lac(−)S. lactis ML-3/2.2. Later, the Muc plasmid, pSRQ2202, was conjugatively transferred from Lac(−) Muc(+)S. cremoris MS04 to Lac(+) nonmucoid S. lactis transconjugant ML-3/2.201. Subsequently, pSRQ2201 and pSRQ2202 were cotransferred from Lac(+) Muc(+)S. lactis transconjugant ML-3/2.202 to Lac(−), nonmucoid, malty S. lactis 4/4.2 and S. lactis subsp. diacetylactis SLA3.25. Transconjugants showing pSRQ2201 were Lac(+); those containing pSRQ2202 were Muc(+). With the transfer of pSRQ2202, the transconjugants S. lactis ML-3/2.202 and S. lactis subsp. diacetylactis SLA3.2501 not only acquired the Muc(+) phenotype but also resistance to bacteriophages, which were lytic to the respective parent strains S. lactis ML-3/2.201 and S. lactis subsp. diacetylactis SLA3.25.